Pentingnya Pendidikan Karakter dalam Membangun Generasi Berintegritas di Era Globalisasi - Adinda Khairunisa; Cut Kumala Sari; Fitri Rahmadani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education plays a crucial role in creating a generation with integrity amidst the rapid pace of global progress. In the era of globalization, the swift changes in social and technological landscapes demand individuals to possess strong character traits, such as integrity, discipline, responsibility, and tolerance, to effectively navigate various moral and social challenges. However, the weak implementation of character values within the education system often leads to an integrity crisis among the youth. This article aims to explore the importance of character education as a fundamental pillar in developing a generation capable of making positive contributions to the global society. The research method used in this study is a literature review, which includes analyzing various theories and studies on character education, as well as the critical roles of families, schools, and communities in the character development process. The analysis reveals that effectively integrated character education can shape individuals who are more responsible, ethical, and empathetic, ultimately strengthening social cohesion and enhancing national competitiveness. Character education not only improves cognitive aspects but also shapes consistent attitudes and behaviors. Therefore, character education should be a primary focus within the educational system, aiming to develop a generation that is not only intellectually smart but also morally upright, enabling them to face global challenges with strong integrity. Keywords: Character education, integrity, globalization.